What is civilization - British Broadcasting Corporation. Television Service (Milton Keynes : Open University, 1971)
The program talks on definations of civilization
Converted into VHS 1/2 in. and U-matic 3/4 in.
Narrated by John Ferguson
Keywords: Civilization -- History; Comparative civilization